Design models of secret reconstruction towards rational users - Hai LIU; Youliang TIAN; Ying TANG; Jianbing Ni; Jianfeng MA (Tongxin xuebao)
Rational Secret Reconstruction is an intersection between traditional secret reconstruction and game theory, which aims to restrict the selfish behaviors of rational users, making both of them obtain the secret in real applications.However, when directly adopting the existing rational secret reconstruction protocols, it is infeasible to realize the fair secret reconstruction.More seriously, an extreme situation may rise, which is some users regard a fake secret as the real one.The crucial reason is that, due to lack of design models, the protocol designers cannot completely consider their selfish behaviors when rational users participate in secret reconstruction.To solve that problem, through the formalizations of rational users and rational secret reconstruction game, the influences of rational users’ action order and their chosen strategies about the fair secret reconstruction were analyzed, and then, three design models for the different scenarios, including purely user rational scenario, reputation-based scenario and trusted user-based scenario, were proposed respectively.Theoretical analysis demonstrates that, the proposed models can help the designers restrict rational users’ selfishness effectively, thereby guiding the designers to devise the fair rational secret reconstruction protocols.Additionally, under the guidance of the proposed models, a fair rational secret reconstruction protocol was devised, which indicated that the proposed models were usable.